Force Majeure in Aircraft Lease Agreement and Covid-19: Indonesian and English Law Perspectives - Hasna Hasna (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2022)
The Covid-19 pandemic has resulted in the establishment of flight restrictions throughout the world. Airlines lose their main source of income. In fact, most aircraft operate from leasing schemes making them unable to fulfill their payment obligations under the aircraft lease agreement. Airlines argue that the Covid-19 pandemic is a force majeure event, is beyond its control, and causes the contractual obligations to be unenforceable. This study reveals Indonesian and British law perspectives on force majeure, related to the Covid-19 pandemic, and analyzes such implementation in the aircraft lease agreement. English law was chosen because most aircraft lease agreements are governed by English law, in accordance with the implementation of the autonomy of the parties of international civil law. This study shows that both Indonesian and English laws regulate force majeure events for the affected party to be released from contract obligations if the party is truly unable to carry out obligations due to force majeure. The event of force majeure must also be regulated specifically in the agreement. However, in the aircraft lease agreement, there is a hell or high-water clause that the obligation to pay rent is absolute regardless of any circumstances. Therefore, the legal provisions regarding force majeure do not apply to aircraft lease agreement unless it is mentioned.DOI: https://doi.org/10.22304/pjih.v9n1.a5